Wich animals do farmers need for tropical mixed systems in the Caribbean ?TT - Quels animaux les agriculteurs ont-ils besoin de systèmes mixtes tropicaux dans les Caraïbes ? - Mandonnet, Nathalie (Institut national de la recherche agronomique (France). Centre de recherches, 2016)
In the South, the improvement of agricultural production is eagerly awaited. Unfortunately, the demand for locally produced fresh meat is not yet being met in the tropics. Indeed, mixed farming systems are the most common (about 80%) and can be a solution to achieve food sovereignty in such limited and isolated areas. The lessons to be learned from these systems are to improve animal performance while respecting the natural balance with the environment and maintaining the multifunctionality of plants and animals. The underlying idea is to give humans and animals their rightful place in the food chain, taking into account the skills and wishes of farmers. This idea is included in the agroecological approach and can provide guidelines for food sovereignty worldwide.